Age-Related Shifts in Theta Oscillatory Activity During Audio-Visual Integration Regardless of Visual Attentional Load - Ren, Yanna; Li, Shengnan; Wang, Tao; Yang, Weiping (Frontiers in Aging Neuroscience, 2020)
Audio-visual integration (AVI) is higher in attended conditions than in unattended conditions. Here, we explore the AVI effect when the attentional recourse is competed by additional visual distractors, and its aging effect using single- and dual-tasks. The results showed the highest AVI effect under single-task-attentional-load condition than under no- and dual-task-attentional-load conditions (all P < 0.05) in both older and younger groups, but the AVI effect was weaker and delayed for older adults compared to younger adults for all attentional-load conditions (all P < 0.05). The non-phase-locked oscillation for AVI analysis illustrated the highest theta and alpha oscillatory activity for single-task-attentional-load condition than for no- and dual-task-attentional-load conditions, and the AVI oscillatory activity mainly occurred in the Cz, CP1 and Oz of older adults but in the Fz, FC1, and Cz of younger adults. The AVI effect was significantly negatively correlated with FC1 (r^2 = 0.1468, P = 0.05) and Cz (r^2 = 0.1447, P = 0.048) theta activity and with Fz (r^2 = 1.557, P = 0.043), FC1 (r^2 = 0.1042, P = 0.008) and Cz (r^2 = 0.0899, P = 0.010) alpha activity for older adults but not for younger adults in dual task. These results suggested a reduction in AVI ability for peripheral stimuli and a shift in AVI oscillation from anterior to posterior regions in older adults as an adaptive mechanism.